EXPLORING GENDER DIFFERENCES IN PERCEIVING ORGANIC PRODUCTS WEBSITE QUALITY: INSIGHTS FROM SERBIA - Ćirić, Maja R (Food and Feed Research, 2024)
The purpose of this research is to investigate whether there is a difference in the valuation of quality organic product website components, including information quality, visual design, and technical adequacy, between men and women. Conducted in Serbia, the methodology comprises surveying 660 participants using a custom questionnaire and analyzing data through descriptive statistics and Chi-square tests. The findings indicate that women assign greater significance to all three aspects of organic product website quality compared to men. Notably, women prioritize information quality, whereas men favour product images. These results carry substantial implications for website developers targeting organic product markets. Addressing the preferences of female consumers is paramount, given their predominant role as the primary purchasers of organic products. Therefore, adapting website characteristics to meet the expectations of female consumers is crucial for maximizing online sales of organic products.